Ruta de biciturismo en la provincia Sugamuxi como estrategia de desarrollo turístico en Boyacá (2023)
The objective of this project is to analyze the bicycle tourism route that connects Sogamoso with Monguí as a tourism development strategy in the Boyacá region, Colombia. This route offers a unique opportunity to highlight the natural, cultural and historical attractions of both locations, promoting active and sustainable tourism. In addition, the tourist promotion of the route is analyzed, proposing effective strategies to make it known nationally and internationally, highlighting its attractions and differentiating it from other tourist destinations. Likewise, the importance of adopting responsible tourism practices is addressed, promoting respect for the natural and cultural environment, and promoting the participation of local communities in tourism management. In order to achieve a bicycle tourism route from Sogamoso to Monguí that is positioned as a potentially successful tourism development strategy for the Boyacá region. Through the creation of the necessary infrastructure, effective tourism promotion and the adoption of responsible tourism practices, it is expected to attract travelers interested in authentic and sustainable experiences, and enhance the economic and social development of local communities.